Miami - Smith, Will; Sony Music Entertainment (New York : Sony Music Entertainment, 1998)
Contains the single taken from the album Big Willie Style.
CD 1 : Album version / (3:19) -- Instrumental / (3:19) -- Callout Hook #1 / (:10) -- Callout Hook #2 / (:10).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Rap (Music).